Habitat preference and distribution of Chinese pangolin and people’s attitude to its conservation in Gorkha District, Nepal - Panta, Melina; Dhami, Bijaya; Shrestha, Bikram; Kc, Nishan; Raut, Nirjala; Timilsina, Yajna Prasad; Khanal Chhetri, Bir Bahadur; Khanal, Sujan; Adhikari, Hari; Varachova, Sona; Kindlmann, Pavel (Frontiers in Ecology and Evolution, 2023)
The Chinese pangolin (Manis pentadactyla) has experienced a rapid population decline throughout its distribution. In Nepal, it mostly occurs outside protected areas; therefore, habitat degradation due to anthropogenic activities is one of the major threats to its survival. However, the scarcity of information on the ecology and distribution of pangolins impedes evidence-based conservation of this species in Nepal. Its habitat preferences and distribution and the factors influencing people’s attitude to its conservation were studied in Gorkha District in central Nepal. Thirteen transects, each 0.5 km in length, were used for recording burrows indicating the presence of pangolin. In total, 124 burrows were recorded, of which 38 were new and 86 were old, which indicated a clumped distribution. Based on the highest percentage frequency of occurrence, most burrows occurred between 650 and 800 m a.s.l., in areas with a south-facing aspect, with moderate canopy cover, in forest, red soil and gentle terrain. The logistic regression model revealed that habitat type, soil type, crown cover, terrain and distance to water were the most important factors affecting pangolin presence. In total, 87 households and nine key informants were interviewed using questionnaires to determine the people’s knowledge of pangolins and attitude to their conservation. More than 50% of the respondents had seen pangolin in the areas studied and had a general knowledge of their habitat and benefits. However, most of them were unaware that it was illegal to hunt pangolins and were involved in opportunistic hunting for meat consumption. This study revealed that an increase in public awareness (mainly through education) would help to increase the likelihood of pangolin survival. These results can also serve as guidelines for protecting pangolin habitats for use by local authorities.